THEORETICAL ANALYSIS OF SINGLE-FIBER TRANSMISSION OVER WDM-PON SYSTEMS - Simatupang, Joni Welman; Pukhrambam, Puspa Devi (Teknologi Indonesia, 2017)
In this paper, a rigorous theoretical analysis on optical beat interferometric (OBI) noises caused by the Rayleigh backscattering (RB) and Fresnel reflection (FR) effects on the performance of a single-fiber single-wavelength WDM-PON (wavelength division multiplexing-passive optical network) transmission system has been presented. Two categories of PON are evaluated: a conventional and a long-reach WDM-PON system. The conventional WDM-PON took place in an access network for a typical transmission distance of 20 km without any optical amplification at the remote node (RN). In this case, the gain of the optimal reflective optical network unit (ONU) will depend on the relative RB power and also the FRs magnitudes and locations along the optical fiber channel/transmission link. However, in the cases of the long-reach WDM-PON deployed at a transmission distance of 100 km or further, the optical amplifiers are indispensable to enhance the optical power budget and to prevent the effect of fiber nonlinearities that may occur at high power injection levels. Although the presence of an optical amplifier (OA) in a long-reach WDM-PON will actually give some additional gain to the whole system, as a result it also produces the worse RB and FR effects to the system itself. A crosstalk to signal (C/S) ratio is used as a key performance indicator of whether the transmission system is in good working order or not. Therefore, this study may provide insight and relevant information in terms of transmission optimization for WDM-PON systems and developments in the future. To educate on the current technologies and developments surrounding conventional and long-reach WDM-PON, a brief overview is provided in the background part of the introduction.